Computational fluid dynamics analysis of greenhouse solar dryer. Issue 8 (17th November 2019) - Purusothaman, M.; Valarmathi, T. N.
ABSTRACT: Innovative technologies are needed to make the life easy. The innovations are best used using renewable source of energy. Greenhouse solar dryer is a device used for drying purpose. Computational fluid dynamics analysis simulation is performed on greenhouse solar dryer when exposed to an ambient temperature on a hot sunny day for free convection and forced convection processes. The mass flow rate and the thickness of polycarbonate roof sheet material vary. The average temperature of the dryer is analysed using simulation. The maximum temperature obtained by forced convection is 71°C for 0.025 kg/s mass flow rate, which is 41% more than that obtained by natural convection.